Italian urban systems: a delimitation - Remo Madella; Giovanni Rabino (European Regional Science Association (ERSA), 2002)
There is a missing concept in the Italian planning tradition: the delimitation of Urban Systems. The laws of the European countries all provide some kind of delimitation for the 'Built Areas', in Italy there are no official boundaries for what it is built. This work tries to fill the gap by applying the work of the French INSEE to the Italian case. This choice is meant for harmonizing the studies on towns or urban entities that all over Europe are split into several research groups. The main aim of the work is the creation of the 'Map of Urban Systems in Italy', done by studying the interactions between administrative boundaries and built areas, and by analyzing the workflows between urban entities. The French methodology turns out to be interesting for its two-level strategy: 1) the physical town - we test if the towns are urban 'continuum' 2) the social and economic town - we test the interaction between core and periphery The output of the work is not only the 'Map of Urban Systems', but also an analysis of the peculiarities of the Italian case (that can surely be used by planners of all administrative levels for their studies).
Keywords: 330